Changing of polyethylene film structure during long-term aging - Yatsyshyn, B. P.; Domantsevich, N. I. (Physics and Chemistry of Solid State, 2020)
The study of surface structure of polyethylene films after their manufacture and later 7 years of closed storage were carried out. Electron-microscopic studies have revealed the features of the structure formation and aging processes, depending on the amount of organic and organic-mineral fillers, as well as the characteristic features of the destruction of the polymer material matrix.